From Desk Set to The Net: Women and Computing Technology in Hollywood Films. - Colatrella, Carol (Canadian Review of American Studies, 2001)
Focuses on the role of science and technology in television and film production in the United States. Economic reason for educating children and general public with science and technology; Description of the technologies of electronic communication; Indication of the statistics from the National Science Foundation.